Notes on the Verb öykün- (< *ö?kün-) - Güzel, Ferdi (Fırat University, 2024)
Old Turkish ötkün- “to imitate; to tell” continues to exist in the same form in some contemporary Turkish dialects today, it is seen as öykün- in the Oghuz group Turkish dialects. In some studies, different verbs with the meanings of “imitating” and “telling” are mentioned. The data in both Old Turkish and Anatolian dialects show that the verb ötkün- “to imitate” also has the meaning of “to tell”. Therefore, as claimed in some studies, there are not two separate verbs, but two related meanings of the same verb. The öykün- form in Oghuz group Turkish dialects reveals that the original of the verb ötkün- is *ö?kün-. The ötkün- form in historical and contemporary dialects emerged as a result of similarity. Many examples in historical dialects where the leaky /d/ sound turns into /t/ as a result of assimilation confirm that this is possible. It is not possible to associate the verb ötkün- with öt- “to make a sound”, both phonetically and semantically. The fact that the primary second sound of the verb is /d/ is the biggest obstacle to associating the word with öt- “to make a sound”. Moreover, the basic meaning of the verb ötkün- is “to imitate”, and a connection cannot be easily established between “making noise” and this meaning. According to the öyk- and ök- data in Anatolian dialects, the base of the verb ötkün- can be designed as *ö?ük-

Eski Türkçe ötkün- “taklit etmek; anlatmak” bugün çağdaş Türk lehçelerinin bir kısmında aynı şekliyle varlığını sürdürmesine rağmen Oğuz grubu Türk lehçelerinde öykün- şeklinde görülür. Bazı çalışmalarda “taklit etmek” ile “anlatmak” anlamlarını taşıyan farklı fiillerden söz edilmektedir. Gerek Eski Türkçede gerekse Anadolu ağızlarında yer alan veriler ötkün- “taklit etmek” fiilinin “anlatmak” anlamının da bulunduğunu göstermektedir. Dolayısıyla bazı çalışmalarda iddia edildiği gibi iki ayrı fiil değil aynı fiilin birbiriyle ilgili iki anlamı söz konusudur. Oğuz grubu Türk lehçelerindeki öykün- biçimi, ötkün- fiilinin aslının *ö?kün- olduğunu ortaya koymaktadır. Tarihi ve çağdaş lehçelerdeki ötkün- biçimi benzeşme sonucu ortaya çıkmıştır. Tarihî lehçelerde sızıcı /d/ sesinin benzeşme sonucu /t/’ye dönüştüğü birçok örnek bunun mümkün olabileceğini doğrulamaktadır. ötkün- fiilinin öt- “ses çıkarmak” ilişkilendirilmesi hem fonetik hem de semantik açıdan mümkün değildir. Fiilin asli ikinci sesinin /?/ olması, kelimeyi öt- “ses çıkarmak” ile ilişkilendirmenin önündeki en büyük engeldir. Ayrıca ötkün- fiilinin temel anlamı “taklit etmek”tir, “ses çıkarmak” ile bu anlam arasında kolay bir bağlantı kurulamaz. Anadolu ağızlarındaki öyk- ve ök- verilerine göre ötkün- fiilinin tabanı *ö?ük- şeklinde tasarlanabilir.
öykün- (< *ö?kün-) FİİLİ ÜZERİNE NOTLAR
Keywords: South-West (Oghuz) Turkic Dialects and Literatures; Güney-Batı (Oğuz) Türk Lehçeleri ve Edebiyatları; Modern Turkic Languages and Literatures (Other); Çağdaş Türk Lehçeleri ve Edebiyatları (Diğer)